Measurement of Hand/Handrim Grip Forces in Two Different One Arm Drive Wheelchairs. (18th June 2014) - Mandy, Anne; Redhead, Lucy; Michaelis, Jon
Abstract : Purpose . The aim of this study was to explore the total and regional grip forces in the hand when propelling two different manual one arm drive wheelchairs: the Neater Uni-wheelchair (NUW) and a foot steered Action3 wheelchair. Methods . 17 nondisabled users were randomly assigned to each wheelchair to drive around an indoor obstacle course. The Grip, a multiple sensor system taking continuous measurement of handgrip force, was attached to the propelling hand. Total grip force in each region of the hand and total grip force across the whole hand were calculated per user per wheelchair. Results . The Action3 with foot steering only generated significantly greater total grip force in straight running compared to the NUW and also in the fingers and thumb in straight running. Conclusions . The results suggest that the Action3 with foot steering generated greater grip forces which may infer a greater potential for repetitive strain injury in the upper limb. Further work is required to explore whether the difference in grip force is of clinical significance in a disabled population.